Perbandingan Quality Of Service Video Conference Bigbluebutton Dan Jitsi - Marwa Miri Al-Haque; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Meetings in an organization are important because meetings means of communication for its organization. Meeting is needed to discuss the agenda or activities to be carried out with members of the organization. The current communication technology supports to hold meeting even in different places. The technology that can be used is web video conferencing. There are two video conferencing web applications that have similar features, Bigbluebutton and Jitsi. This application has a difference in Quality of Service, so a comparison of QOS Bigbluebutton and Jitsi on Ubuntu 16.04 is to make it easier for users to choose effective applications to use.Keywords: Meeting, Video Conference, Quality of Service, Ubuntu 16.04